Pengaruh Formulasi Basis Terhadap Uji Fisik Sediaan Krim Ekstrak Etanol Daun Sirih Merah (Piper crocatum) - Anggi Pratiwi; Anom Parmadi; Siwi Hastuti (Indonesian Journal on Medical Science, 2022)
Red betel leaf has an antifungal effect because red betel leaf contains chemical compounds such as flavonoids, alkaloids, saponins, polyphenols, tannins, terpenoids and essential oils. This research is an experimental research conducted in the laboratory with maceration method using 70% ethanol as solvent. The yield obtained from the extraction by maceration was 8.66 % w/w. The organoleptic results of cream preparations are brownish green, smell of jasmine, pH 6 test, homogeneity test is homogeneous, cream type is A/M and cream provides protection against alkaline solutions, the panelist preference test was chosen formula 3 because it has the largest number of panelists preference levels . In the dispersion test, the results of the ANOVA test showed a significance value (p 0.000) <0.05. This shows that there is an effect of the base formulation on the physical test of the cream preparation from the spreadability test of each formula. In the adhesion test, the ANOVA test results showed a significance value (p 0.530) > 0.05. These means that there was no effect of the base formulation on the adhesion test of each formula. Formulation 3 with a combination of 3.34 g stearic acid base and 0.43 g feather fat was the best and most stable formulation in the evaluation test of red betel leaf ethanol extract cream.